Establishing the National Chlamydia Screening Programme in England: results from the first full year of screening. Issue 5 (30th September 2004) - LaMontagne, D S; Fenton, K A; Randall, S; Anderson, S; Carter, P
Abstract : Background: The phased implementation of the National Chlamydia Screening Programme (NCSP) began in September 2002. The NCSP offers opportunistic screening for chlamydia to women and men under 25 years of age attending clinical and non-clinical screening venues using non-invasive urine or vulvo-vaginal swab samples tested via nucleic acid amplification. This review describes the implementation of the NCSP, reports positivity rates for the first year, and explores risk factors for genital chlamydial infection. Methods: Cross sectional study of the first year's screening data from the NCSP. A standardised core dataset for each screening test was collected from 302 screening venues, excluding genitourinary medicine (GUM) clinics, across 10 phase 1 programme areas. We estimated chlamydia positivity by demographic and behavioural characteristics, and investigated factors associated with infection through univariate and multivariate analyses. Results: Chlamydia positivity among people under 25 years of age screened in non-GUM settings was 10.1% (1538/15 241) in women and 13.3% (156/1172) in men. Risk factors varied by sex: for women—age 16–19, non-white ethnicity, and sexual behaviours were associated with infection; for men—only age 20–24 and non-white ethnicity were associated with infection. Discussion: In the first phase of the NCSP, 16 413 opportunistic screens among young adults under 25 years of age were performed at non-GUM settings and testing volume increased over time. Rates of disease were similar to those found during the English screening pilot and were comparable to the first year of widespread screening in Sweden and the United States. The screening programme in England will continue to expand as further phases are included, with national coverage anticipated by 2008.